Drug reaction with eosinophilia and systemic symptoms syndrome with toxic epidermal necrolysis: Overlap in an HIV seropositive male with diffuse large "B" cell lymphoma - A rare case report - Neelam Kumari Bhatt; Vasudha A Belgaumkar; Ravindranath B Chavan; Nitika S Deshmukh (Wolters Kluwer Medknow Publications, 2023)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a severe drug-induced hypersensitivity reaction with varied presentations. We report a rare case of DRESS syndrome with toxic epidermal necrolysis (TEN) overlap associated with non-Hodgkin lymphoma (NHL). A 52-year-old male with retroviral disease presented with fever and diffuse skin peeling with mucosal erosions. The patient was on antitubercular therapy (ATT) for 1 month for suspected tubercular cervical lymphadenitis. He had facial edema, extensive skin tenderness, and denudation with a positive Nikolsky's sign, icterus, hepatosplenomegaly and multiple enlarged immobile nontender cervical, and axillary and inguinal lymph nodes. Investigations showed leukocytosis with hepatic and renal dysfunction. Skin histopathology was consistent with TEN. Based on Registry of Severe Cutaneous Adverse Reaction criteria, a diagnosis of ATT-induced DRESS with TEN overlap was made. Cervical lymph node biopsy and immunohistochemistry confirmed diffuse large B-cell NHL. ATT was withheld and the patient was treated with systemic steroids and assessed for initiation of chemotherapy. The profound immunological dysregulation in individuals with retroviral disease leads to varied clinical presentations, increasing the chances of diagnostic errors, and culminating in challenging scenarios. Therefore, seemingly innocuous symptoms and signs warrant thorough evaluation. Sound clinical acumen and prompt investigations for unusual causes such as malignancies can improve outcomes by aiding accurate diagnosis as well as avert untoward complications such as DRESS syndrome/TE.